Comparison of transvaginal sonography with hysteroscopy and correlation with histopathological report in case of abnormal uterine bleeding - Maiti, Gunadhar; Lele, Prasad; Borse, Dhananjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding (AUB) is change in frequency of menses, duration of flow or amount of blood loss. The objectives of the present study were to determine and compare the diagnostic accuracy of TVUS (Transvaginal ultrasonogrphy) with hysteroscopy for diagnosis of endometrial and intramyometrial pathology in case of abnormal uterine bleeding, to study the correlation with histopathological report of endometrial biopsy Methods: It was a prospective comparative study. 200 cases of AUB were selected from June 2010 to May 2012 attending Gynaecology OPD in tertiary care level public sector teaching hospital at Mumbai, meeting the selection criteria were enrolled into the study. Complete history, detail general, systemic and local examination was performed for all patients. Two-dimensional transvaginal ultrasonography was performed to see for endometrial or intramyometrial pathology. Endometrial thickness was noted for all patients. Hysteroscopy and D&C was performed within 48 hours of ultrasonography. After hysteroscopy, curettage was performed and sent for histopathological examination. Results: TVUS detected, 19 polyps (9.5%) and 81 myomas. It was able to differentiate these myomas as 64 interstitials (32%) and 17 submucous (8.5%) hysteroscopy detected 26 submucous myomas (13%), 31 polyps (15.5%), endometrial hyperplasia detected by TVUS, 19 in premenopausal and 06 in postmenopausal age group. Hysteroscopy detected 24 in premenopausal and 06 in post-menopausal age group. Histopathology of endometrial biopsy it came positive for 13 in premenopausal and 08 in postmenopausal age group. Two cases of CA endometrium were diagnosed on HPE out of which one was diagnosed by TVUS and same was diagnosed by hysteroscopy. Conclusions: TVUS has significantly lower sensitivity but comparable specificity with hysteroscopy in diagnosing endometrial polyp and submucous fibroid, comparable sensitivity and specificity in diagnosing endometrial hyperplasia, equivalent sensitivity and specificity in diagnosing endometrial carcinoma, accuracy of TVUS for detecting pathology in AUB is comparable to hysteroscopy, suitable for developing countries as first diagnostic step for AUB.